Dose-dependent interaction of two heavy metals with amiodarone toxicity in Saccharomyces cerevisiae. (May 2022) - Halloum, Iman; Al-Attrache, Houssein; El-Ghoz, Katia; Hammoud, Lara; Abdel-Razzak, Ziad
Amiodarone (AMD) is an antiarrhythmic drug that induces idiosyncratic toxicity. Environmental pollutants, including heavy metals, could interact with its toxicity by affecting pharmacokinetics and pharmacodynamics. Other levels of interaction could exist in yeast, such as oxidative stress and the general stress response. In this study, we investigated the interaction of mercury chloride (HgCl2 ) and cadmium chloride (CdCl2 ) with AMD toxicity on Saccharomyces cerevisiae . Interaction type - synergistic, additive, or antagonistic - was determined by median drug effect analysis using "CompuSyn". HgCl2 potentiated AMD toxicity at high doses (≥ 71.4 μm, which yielded more than 60% inhibition). CdCl2 acted similarly at high doses (≥ 57.9 μm ). An antagonistic effect appeared at lower doses with both heavy metals (≤ 49.4 μm for HgCl2 and AMD; ≤ 18.9 μm for CdCl2 and AMD). The threshold concentrations (HgCl2 or CdCl2 combined with AMD) that switched the interaction from antagonistic to additive, and then to synergistic, were decreased in the yeast strain mutant in catalase ( CTT1), suggesting an important role for this enzyme. Moreover, mutation of the nutrient sensing receptor gene GPR1 caused the synergistic interaction of CdCl2, but not HgCl2, with AMD to occur at the lowest tested concentrations (1.2 μm ). The reverse was obtained with the mutant strain in calcium–manganese transporter gene PMR1, where the synergistic interaction of HgCl2 with AMD occurred at concentrations (20.7 μm ) lower than that of the wild type (71.4 μm ). These results demonstrated a dose-dependent interaction between the two heavy metals with AMD toxicity, and the involvement of oxidative stress, calcium homeostasis, and nutrient sensing in the observed interaction.